The Influence of Principal Leadership and Work Motivation on Teacher Performance at SMA N 1 Tanjung Agung - Karespa Beliani; Yasir Arafat; Hery Setiyo Nugroho (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to analyze the influence of principal leadership and work motivation on teacher performance at SMA Negeri 1 Tanjung Agung. The research method used is quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to teachers as research respondents. The results of the analysis show that the leadership of the principal has a positive and significant influence on teacher performance. In addition, work motivation also contributes significantly to improving teacher performance. Simultaneously, the principal's leadership and work motivation have a significant effect on teacher performance. The implications of this study show that improving the quality of school principals' leadership and work motivation can be an effective strategy in improving teacher performance in the school environment.